2020
DOI: 10.1186/s13256-020-02452-3
|View full text |Cite
|
Sign up to set email alerts
|

Hilar lymphadenopathy, a novel finding in the setting of coronavirus disease (COVID-19): a case report

Abstract: Background: As the outbreak of coronavirus disease 2019 (COVID-19) has progressed, computed tomography has emerged as an integral part of the diagnosis alongside reverse transcriptase-polymerase chain reaction assays. Frequently encountered imaging findings include peripheral airspace consolidations; bilateral ground-glass opacities; and, less commonly, cavitation. Hilar lymphadenopathy is a rarely reported finding in the setting of COVID-19. Case presentation: A 73-year-old Caucasian woman presented to our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The incidence of hilar lymphadenopathy in our study was 0.6%. In the available current literature, only one case report with hilar lymphadenopathy has been reported in COVID-19 [ 39 ]. Few studies showed no presence of hilar lymphadenopathy in COVID-19 [ 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of hilar lymphadenopathy in our study was 0.6%. In the available current literature, only one case report with hilar lymphadenopathy has been reported in COVID-19 [ 39 ]. Few studies showed no presence of hilar lymphadenopathy in COVID-19 [ 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal lymphadenopathy previously thought to be an atypical feature has been redefined as “not-atypical” feature of COVID-19 [ 7 , 41 ]. However, hilar lymphadenopathy which is usually associated with fungal infections, mycobacterial infections, and sarcoidosis are seldom seen in COVID pneumonia [ 39 ]. Histopathological correlation was unavailable for our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the report of the mediastinal LA in 15 COVID-19 patients admitted to the intensive care unit has also been described following the chest CT scan diagnosis in France [ 26 ]. Hilar LA is regularly observed during sarcoidosis, fungal and mycobacterial infections [ 27 ]. However, according to the recent report from the US Monmouth Medical Center, a 73-year-old Caucasian woman with typical symptoms of COVID-19 was diagnosed as an infected patient upon determining the positive result of the RT-PCR test.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the recent report from the US Monmouth Medical Center, a 73-year-old Caucasian woman with typical symptoms of COVID-19 was diagnosed as an infected patient upon determining the positive result of the RT-PCR test. Notably, chest CT scan examination also displayed an atypical bilateral hilar LA, as well as focal consolidations, besides the multifocal subpleural ground-glass opacities [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 manifestations are polymorphic and highly variable, both clinically and radiologically. Clinical presentations include DL involving cervical, subcarinal, and superior-mediastinal lymph nodes, mainly in severe COVID-19 cases [ 1 , 2 ]. Other reports show multiple cervical lymphadenopathies during the symptomatic phase of the disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%